Platelet transfusions and thrombocytopenia in intensive care units: Protocol for an international inception cohort study (PLOT‐ICU). Issue 9 (23rd August 2022) - Anthon, Carl Thomas; Pène, Frédéric; Perner, Anders; Azoulay, Elie; Puxty, Kathryn; Van De Louw, Andry; Barratt‐Due, Andreas; Chawla, Sanjay; Castro, Pedro; Povoa, Pedro; Coelho, Luis; Metaxa, Victoria; et al.
Abstract: Introduction: Thrombocytopenia is frequent in intensive care unit (ICU) patients and has been associated with worse outcome. Platelet transfusions are often used in the management of ICU patients with severe thrombocytopenia. However, the reported frequencies of thrombocytopenia and platelet transfusion practices in the ICU vary considerably. Therefore, we aim to provide contemporary epidemiological data on thrombocytopenia and platelet transfusion practices in the ICU. Methods: We will conduct an international inception cohort, including at least 1000 acutely admitted adult ICU patients. Routinely available data will be collected at baseline (ICU admission), and daily during ICU stay up to a maximum of 90 days. The primary outcome will be the number of patients with thrombocytopenia (a recorded platelet count < 150 × 10 9 /L) at baseline and/or during ICU stay. Secondary outcomes include mortality, days alive and out of hospital, days alive without life‐support, the number of patients with at least one bleeding episode, at least one thromboembolic event and at least one platelet transfusion in the ICU, the number of platelet transfusions and the indications for transfusion. The primary and secondary outcomes will be presented descriptively. In addition, we will assess risk factors for developing thrombocytopenia during ICU stay and the association between thrombocytopenia at baseline and 90‐day mortality using logistic regression analyses. Conclusion: The outlined international PLOT‐ICU cohort study will provide contemporary epidemiological data on the burden and clinical significance of thrombocytopenia in adult ICU patients and describe the current platelet transfusion practice.